2017
DOI: 10.9787/pbb.2017.5.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heat Shock Proteins by Heat Stress in Soybean

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Heat stress is one of the factors disturb productivity and growth of plants. Many genes including heat shock protein (HSP), heat shock transcription factors (HSF) and chaperones, were identified and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, our result revealed that HSP20 and HSP70 were down regulated by heat stress at BA site. As HSPs have been shown to be expressed more under heat stress over short time periods [48, 49] it seemed that in our study HSP20 and HSP70 genes might had responded for short time period after transplanting plants under heat stress at BA site but decreased with time.…”
Section: Discussionmentioning
confidence: 74%
“…However, our result revealed that HSP20 and HSP70 were down regulated by heat stress at BA site. As HSPs have been shown to be expressed more under heat stress over short time periods [48, 49] it seemed that in our study HSP20 and HSP70 genes might had responded for short time period after transplanting plants under heat stress at BA site but decreased with time.…”
Section: Discussionmentioning
confidence: 74%
“…Earlier studies that focused on transcriptome profiling indicated that heat shock proteins may play an important role in improving the tolerance of soybean subjected to heat stress [ 21 , 22 ]. To examine if different growing temperatures had any effect on heat shock protein (HSP) accumulation, we conducted western blot analysis using antibodies specific for HSP70 and HSP17.6.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies that focused on transcriptome profiling indicated that heat shock proteins may play an important role in improving the tolerance of soybean subjected to heat stress [21,22]. To examine if different growing temperatures had any effect on heat shock protein (HSP) accumulation, The superimposed color images generated by Delta2D software facilitates the identification of differences between the two treatments where yellow demonstrates similar protein quantities in both growing temperatures.…”
Section: Effect Of Heat Stress On the Accumulation Of Hsp70 Hsp176 And Bip In Seeds Of Heat-tolerant And Heat-sensitive Genotypesmentioning
confidence: 99%
“…As a result, small HSP families were found to be upregulated and expressed in prolonged heat stress conditions. These findings provided valuable information about heat tolerance in soybean ( Song et al, 2017 ). Heat shock TFs play a key role in helping soybean plants in extreme heat stress episodes.…”
Section: Transcription Factors For Heat Tolerance In Soybeanmentioning
confidence: 86%
“…Soybean plants with enhanced tolerance to heat stress showed overexpression of GmEF8 in hairy roots and had a high proline level compared to plants with control hairy roots ( Zhang et al, 2022a ). Earlier, Song et al (2017) performed an RNA-seq analysis using two soybean varieties under extreme stress. They analyzed the transcripts and obtained 2,458 differentially expressed genes.…”
Section: Transcription Factors For Heat Tolerance In Soybeanmentioning
confidence: 99%